2004
DOI: 10.1677/jme.0.0320583
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibition and estrogen receptor alpha levels modulate the transcriptional activity of partial antiestrogens

Abstract: In this study, we have analysed the effects of histone deacetylase (HDAC) inhibition on estrogen receptor (ER) expression and on its transcriptional activity in response to antiestrogens. In several breast cancer cell lines, trichostatin A (TSA), a potent HDAC inhibitor, strongly decreases ER expression in a dose-dependent manner. This repression is observed independently of the presence of ligand and also occurs in ovarian and endometrial cell lines. In addition, we show that in MCF7 cells bearing a stably tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
35
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 50 publications
10
35
1
Order By: Relevance
“…In agreement with previous observations (Huang et al 2000, Chopin et al 2002, Margueron et al 2004, HDACi caused an important increase of p21…”
Section: Endocrine-related Cancersupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with previous observations (Huang et al 2000, Chopin et al 2002, Margueron et al 2004, HDACi caused an important increase of p21…”
Section: Endocrine-related Cancersupporting
confidence: 93%
“…Also in agreement with the antagonism on cyclin D1 induction, HDACi were able to block E 2 -dependent pRb phosphorylation, demonstrating again the strong anti-proliferative effects of these inhibitors in estrogen-dependent breast cancer cells. In relation to this, it has been shown that ER-positive breast cancer cells are more sensitive to the HDACi TSA than ER-negative cells (Reid et al 2003, Alao et al 2004, Margueron et al 2004.…”
Section: Endocrine-related Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…We show here that SAFB action is specifically affected by four different HDAC inhibitors, depending on the receptor tested (FXR or PPAR). Although these results may appear confusing at first sight, they most probably reflect the recruitment of different types of HDACs by each receptor, as well as some specific interplay between HDACs on the one hand and promoters and ligands on the other hand, as recently exemplified with the estrogen receptor (ER), whose action is differently modulated by HDAC inhibitors, depending upon the cell line and the ligand tested (Margueron et al 2004). It is also possible that these compounds have some side effects and modulate other cellular components which indirectly affect the transcription of the reporter construct.…”
Section: Discussionmentioning
confidence: 99%
“…In breast tumor models, HDIs have potent antiproliferative effects in vitro and in vivo and interfere with estrogen signaling (13)(14)(15)(16)(17). Estrogens effects are mediated by two distinct estrogen receptors, ERa and ERh, acting as transcriptional factors that belong to the nuclear receptor superfamily (18).…”
Section: Introductionmentioning
confidence: 99%